The Use of Lecturer’s Written Feedback in Writing Class - Hukom, Salmon J; Huninhatu, Felmi Benyamin (MATAI: International Journal of Language Education, 2023)
This paper endeavors to propose lecturer-written feedback as an innovative approach within the writing class setting. The feedback methodology comprises two distinct types: direct and indirect feedback (coded and un-coded). Direct written feedback stands out due to its impactful nature, fostering a deeper comprehension among students regarding the feedback's significance provided by the lecturer. Moreover, it prompts students to initiate their efforts toward understanding the feedback, even if their prior knowledge is limited or relatively low. Conversely, indirect written feedback, while not offering comprehensive explanations, serves as a catalyst for encouraging students to independently identify and rectify their errors. Notably, various researchers have delved into this approach, unveiling its potential benefits. Findings from these studies highlight the advantages of lecturer-written feedback in significantly enhancing students' writing skills.